2015
DOI: 10.1186/s12865-014-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive T-cell therapy of prostate cancer targeting the cancer stem cell antigen EpCAM

Abstract: BackgroundAdoptive transfer of tumor infiltrating or circulating lymphocytes transduced with tumor antigen receptors has been examined in various clinical trials to treat human cancers. The tumor antigens targeted by transferred lymphocytes affects the efficacy of this therapeutic approach. Because cancer stem cells (CSCs) play an important role in tumor growth and metastasis, we hypothesized that adoptive transfer of T cells targeting a CSC antigen could result in dramatic anti-tumor effects.ResultsAn EpCAM-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 20 publications
2
130
0
Order By: Relevance
“…The spacers used in China are mainly CH 2 CH 3 , Fc hinge, and CD8 hinge (Deng et al, 2015;Guo et al, 2015;Wang et al, 2013) (Table 1). Recently, it has been reported that CH 2 CH 3 spacer could bind soluble Fc-receptors and cause off-target cell lysis (Almåsbak et al, 2015), and that the mutation or deletion of the CH 2 region could obviate this problem.…”
Section: Car Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spacers used in China are mainly CH 2 CH 3 , Fc hinge, and CD8 hinge (Deng et al, 2015;Guo et al, 2015;Wang et al, 2013) (Table 1). Recently, it has been reported that CH 2 CH 3 spacer could bind soluble Fc-receptors and cause off-target cell lysis (Almåsbak et al, 2015), and that the mutation or deletion of the CH 2 region could obviate this problem.…”
Section: Car Constructsmentioning
confidence: 99%
“…Also, other modifications are also introduced into CAR-T cells, such as CD137 co-stimulatory ligand expression (Zhao et al, 2015), bi-specific antigen recognition targeting prostate specific membrane antigen (PSMA) and prostate stem cell antigen (PSCA) (Kloss et al, 2013), and extracelluar matrix degradation with heparanase (Caruana et al, 2015) etc.. Recently, an on-switch CAR paradigm was also developed, which allowed the activation of CAR-T cells to be controlled by small molecules (Wu et al, 2015). Although the next generation strategies help to improve the function of CAR-T cells, they also increase the difficulty of gene modification, and the safety and efficacy of these newly developed constructs have yet to be established in human studies (Chmielewski and Abken, 2015).…”
Section: Car Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical models have been developed as a proof of concept that CARs could also be used to target CSCs. [57] Deng et al, [58] for instance, demonstrated that CAR T cell therapy could inhibit tumor growth of highly metastatic prostate cancer that expresses low levels of EpCAM. Other CSC-targeting adoptive T cell therapies include CAR T cells which bind to a CSCspecific N-glycosylation-dependent epitope of CD133, [59] high-molecular weight melanoma associated antigen or chondroitin sulfate proteoglycan 4-specific CAR T cells that were reported to specifically eliminate melanoma with a CSC phenotype, [60,61] and epidermal growth factor receptor variant III (EGFRvIII) specific CAR T cells which target glioma SCs.…”
Section: Enhancing Immune Responsesmentioning
confidence: 99%
“…CAR T cells @ C I C E d i z i o n i I n t e r n a z i o n a l i against PSMA (otherwise known as glutamate-carboxypeptidase) can specifically target in vitro such antigen-expressing cells and in vivo kill the tumor cells. In concurrent addition to CAR T cell adoptive immunotherapy,an administration of interleukin-2 (IL-2) may further increase immune responses (29,(48)(49)(50)(51)(52).…”
Section: Adoptive T-cell Transfermentioning
confidence: 99%